A new optimization uniformity for indoor visible light communication systems using optical attocells configuration - Mohammed Gismalla, Mohammed Salih (2021)
The demand for high data rate, capacity, increasing user mobility as well as low power consumption is increasing daily, where it is considered as main the challenges facing the radio frequency (RF) technology. Therefore, an alternative technology called visible light communications (VLC) was adopted to overcome these challenges. This technology is expected to support 5G and beyond due to its high and free frequency offered, as well as robust security. The main problem of this research is, the distribution of a few numbers of optical attocells on the ceiling have caused multiple blind areas in the room, and resulted in nonuniformity distribution. Besides that, employing large numbers of optical attocells has caused a severe ISI, which degrades the system performance, and produced large RMS delay. Therefore, to avoid this problem, a new arrangement of optical attocells, in addition to optimizing the VLC system parameters is proposed. In this research, the proposed arrangement of optical attocells configuration models will improve the uniformity in terms of received power and SNR. The SAAHP, FOV, and CV are used to study the behavior of the two proposed models. The average received power of 2.85 dBm is obtained for the proposed Model Basic 2 that consists of 13 optical attocells, which varies from -0.57 to 4.92 dBm. Moreover, the average SNR of 75.37 dB is obtained for the proposed Model Basic 2, which varies from 68.52 to 79.5 dB. The maximum of received power and SNR is obtained at the center of the room. The better uniformity (CV) of 0.374 and 0.0283 are obtained for the received power and SNR respectively. Additionally, six various modulation techniques are studied to evaluate the proposed models, all modulations produced better BER (≤10−6) at data rate 30 Mbps, while the higher order modulations (L-PPM and M-PAM) produced higher data rate reaching up to 100 Gbps with a BER ≤10−6. This research also investigated an industrial warehouse model with different heights level, where a data rate of 30 Mbps is achieved with acceptable received power and SNR respectively. A BER ≤10−6 is obtained with L-PPM and M-PAM modulation techniques.